The aquatic macrophytes as refuge, nursery and feeding habitats for freshwater fish from Cabiúnas Lagoon, Restinga de Jurubatiba National Park, Rio de Janeiro, Brazil - Sánchez-Botero, Jorge Iván (2007)
In several aquatic ecosystems, macrophyte areas represent important refuge, feeding or nursery habitats for aquatic organisms. These functional roles are attributed, mainly, to the associated food availability and to the structural complexity that promotes protection and a diversity of microhabitats. Considering the high density and richness of aquatic macrophytes at Cabiúnas coastal lagoon (RJ), the present study intends to identify the possible ways in which the fish assemblages use these habitats. Hence, some aspects of feeding habits, size distribution and life stages of the fish species were evaluated. During one year, fish were monthly sampled using seine nets in macrophyte banks from Cabiúnas lagoon. A total of 1,596 individuals from ten species were collected, the most abundant (97.3%) being the cichlid Cichlasoma facetum and the minute fishes Hyphessobrycon bifasciatus, H. luetkenii and Poecilia vivipara. Six species, that represented 97.9% of the total abundance, are classified in the omnivorous guild, suggesting that these environments are favorable to species with a high feeding plasticity. Moreover, the main feeding items consumed were highly available in the macrophyte banks from this same lagoon, demonstrating their role as feeding areas. Adult individuals were more abundant (c 2=166.61; p=0.0001), however the higher proportion of juveniles registered for medium to large-sized fish species suggests a use of the banks as nurseries. On the other hand, minute species occurred in high abundance, as both juveniles and adults, during the entire studied period, indicating an association with macrophytes throughout their ontogeny. In fact, these minute fishes are more prone to predation, indicating the macrophyte banks as favorable refuges. Key-words:, Restinga de Jurubatiba